Patlayıcı maddeler ile basamak kazı tasarımı parametrelerinin incelenmesi ve PATAS uzman sisteminin denenmesi - Coşkun, Orhan (Fen Bilimleri Enstitüsü, 1995)
Madencilik ' de üretimin başlangıç noktası olan patlatma ekonomiklik ile çok yakından ilgilidir. Ekonomiklik ve verimi yükseltmek için daha mükemmel tasarımlara ulaşmak maksadıyla bir çok araştırma yapılmış, teoriler geliştirilmiştir. Bu tez çalışması kapsamında öncelikle patlatma tasarımı için geliştirilmiş çeşitli teoriler anlatılmış, tasarımda kullanılan parametreler incelenmiştir. Daha sonra yeni bir bilgisayar yazılımı olan Uzman Sistemler ve özellikleri anlatılmıştır. Son aşamada ise patlatma tasarımı amacıyla geliştirilmiş PATAS isimli uzman sistem tanıtılarak denemesi yapılmış ve pratik olarak kullanılabilirliği araştırılmıştır.

The use of explosives for rock blasting began in 1627 in the gold mines of Hungary with black powder. The use of black powder to break rock was much faster and more efficient than the traditional methods of firs setting which had been used before that time. Blasting has become an accepted technique for rock fragmentation worldwide. Most mining and construction operations use blasting. The feasibility and economy of many types of mining ventures and costruction projects depend the use of explosives. The blasting industry is rapidly chancing with new theories, products and techniques. Many blasting procedures and technique have been proposed since blasting began. This thesis concentrates on surface blast design. When blasting first began, there was little known about the side effect of blasting. Now, explosive users want to break rock safely, efficiently and economically with the minimum amount of air blast,ground vibration and violence. Many theories have been proposed as to how and why rock breaks as a result of an explosion. Two seperate and distinct mechanism occur. The explosion first induces a stress wave, which is compressional wave, into the rock surrounding the charge, IX Expert systems salve problems that are normally solved by human "experts" To solve expert-level problems, expert systems need access to substantial domain knowledge base, which must be built as efficiently as possible. Expert systems also need to exploit one or more reasoning mechanism to apply their knowledge to the problems they are given. Then they need a mechanism for explaining what they have done to users who rely on them, Expert systems are being used in a wide variety of applications including diagnosis, planning, forecasting, design, interpretation, control, status, monitoring and instruction. In third chapter, the history of Expert systems, basic concepts of expert systems, the structure of expert systems, types of expert systems, advantage and disadvantage of expert systems, how expert systems work, which problems can solve with expert systems are tried to be explain. At the end of the third chapter some expert system application had been introduced which are used in mining industry. Knowledge is very important for expert systems. Because they use knowledge for solving problems. Know ledge base shows the power of the expert systems. So knowledge acquisition is most important for the expert system. In fourth chapter methods and ways of knowledge acquisition had been explained. At the end of this part the research of knowledge acquisation had been discussed. One of the most important knowledge acquisation method was searching the application of bench blasting in Turkey. For this reason a special question sheets had prepared and sent to the mines which uses blasting techniques. XI Expert systems salve problems that are normally solved by human "experts" To solve expert-level problems, expert systems need access to substantial domain knowledge base, which must be built as efficiently as possible. Expert systems also need to exploit one or more reasoning mechanism to apply their knowledge to the problems they are given. Then they need a mechanism for explaining what they have done to users who rely on them, Expert systems are being used in a wide variety of applications including diagnosis, planning, forecasting, design, interpretation, control, status, monitoring and instruction. In third chapter, the history of Expert systems, basic concepts of expert systems, the structure of expert systems, types of expert systems, advantage and disadvantage of expert systems, how expert systems work, which problems can solve with expert systems are tried to be explain. At the end of the third chapter some expert system application had been introduced which are used in mining industry. Knowledge is very important for expert systems. Because they use knowledge for solving problems. Know ledge base shows the power of the expert systems. So knowledge acquisition is most important for the expert system. In fourth chapter methods and ways of knowledge acquisition had been explained. At the end of this part the research of knowledge acquisation had been discussed. One of the most important knowledge acquisation method was searching the application of bench blasting in Turkey. For this reason a special question sheets had prepared and sent to the mines which uses blasting techniques. XI At the end of the thesis, it has discussed that the "PATAS" could use in mining industry. Blasting theory is perhaps one of the most inte resting thought- provoking, challenging and cantrol- versial areas of mining industry. It encompasses many areas in the science of chemistry, physics, thermodynamics, shock wave interaction and rock mechanics. In broad terms, rock breakage by explasives involves the action of an explosive and the response of the surrounding rock mass within the realms of energy, time and mass. In spite of the tremendous amount of research conducted in the last few decades, no single blasting theory has been developed and accepted that adequately explains the mechanisms of rock breakage in all blasting conditions and material types. There is as yet no consistent and widely appli cable theory of blasting. But the porpose of the science is find the new, reach the excellent. This thesis prepared for this reason. X11X Expert systems salve problems that are normally solved by human "experts" To solve expert-level problems, expert systems need access to substantial domain knowledge base, which must be built as efficiently as possible. Expert systems also need to exploit one or more reasoning mechanism to apply their knowledge to the problems they are given. Then they need a mechanism for explaining what they have done to users who rely on them, Expert systems are being used in a wide variety of applications including diagnosis, planning, forecasting, design, interpretation, control, status, monitoring and instruction. In third chapter, the history of Expert systems, basic concepts of expert systems, the structure of expert systems, types of expert systems, advantage and disadvantage of expert systems, how expert systems work, which problems can solve with expert systems are tried to be explain. At the end of the third chapter some expert system application had been introduced which are used in mining industry. Knowledge is very important for expert systems. Because they use knowledge for solving problems. Know ledge base shows the power of the expert systems. So knowledge acquisition is most important for the expert system. In fourth chapter methods and ways of knowledge acquisition had been explained. At the end of this part the research of knowledge acquisation had been discussed. One of the most important knowledge acquisation method was searching the application of bench blasting in Turkey. For this reason a special question sheets had prepared and sent to the mines which uses blasting techniques.
Researching For Bench Blasting Desing Parameters And Testing The "potas" Expert System
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1995
Keywords: Kazı performansı; Patlayıcı maddeler; Uzman sistemler; Excavation performance; Explosives; Expert systems